Safe and effective treatment of spontaneous neoplasms with interleukin 12 electro‐chemo‐gene therapy. Issue 3 (27th January 2015) - Cutrera, Jeffry; King, Glenn; Jones, Pamela; Kicenuik, Kristin; Gumpel, Elias; Xia, Xueqing; Li, Shulin
Abstract Electroporation improves the anti‐tumour efficacy of chemotherapeutic and gene therapies. Combining electroporation‐mediated chemotherapeutics with interleukin 12 (IL‐12) plasmid DNA produces a strong yet safe anti‐tumour effect for treating primary and refractory tumours. A previously published report demonstrated the efficacy of a single cycle of IL‐12 plasmid DNA and bleomycin in canines, and, similarly, this study further demonstrates the safety and efficacy of repeated cycles of chemotherapy plus IL‐12 gene therapy for long‐term management of aggressive tumours. Thirteen canine patients were enrolled in this study and received multiple cycles of electro‐chemo‐gene therapy (ECGT) with IL‐12 pDNA and either bleomycin or gemcitabine. ECGT treatments are very effective for inducing tumour regression via an antitumour immune response in all tested histotypes except for sarcomas, and these treatments can quickly eradicate or debulk large squamous cell carcinomas. The versatility of ECGT allows for response‐based modifications which can overcome treatment resistance for affecting refractory lesions. Importantly, not a single severe adverse event was noted even in animals receiving the highest doses of chemotherapeutics and IL12 pDNA over multiple treatment cycles. This report highlights the safety, efficacy and versatility of this treatment strategy. The data reveal the importance of inducing a strong anti‐tumour response for successfully affecting not only the treated tumours, but also non‐treated metastatic tumours. ECGT with IL12 pDNA plus chemotherapy is an effective strategy for treating multiple types of spontaneous cancers including large, refractory and multiple tumour burdens.